2020
DOI: 10.31234/osf.io/paxh4
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The role of orthographic neighbourhood effects in lateralized lexical decision: A replication study and meta-analysis.

Abstract: Orthographic neighbourhood size (N) effects differ under lateralized presentation. Evidence suggests a facilitatory effect of N in the right hemisphere. However, the effect of N in the left hemisphere remains controversial: it may have a weaker facilitative role or it may even be inhibitory. In a pre-registered online experiment, we aimed to replicate the interaction between N and visual field and provide support for an inhibitory effect of N in the left hemisphere. We subsequently conducted a pre-registered s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Information presented in the left visual field (LVF) that is projected to the right hemisphere may be initially processed less efficiently (e.g., by serial orthographic analysis; Brand et al, 1983;Ellis et al, 1988;Eng & Hellige, 1984), and must be transferred to the left hemisphere via the corpus callosum, resulting in slower processing and/or some loss in fidelity. Consistent with this account, evidence that orthographic neighborhood (N) effects are larger and facilitatory in the LVF and weaker and inhibitory in the RVF (see Parker et al, 2021, for a review) may reflect stronger top-down activation from the word level within an interactive system for letter strings in the LVF. Words in the LVF would then suffer from slower and more error-prone bottom-up processing due to interhemispheric transfer.…”
Section: Visual Field Asymmetrymentioning
confidence: 89%
See 1 more Smart Citation
“…Information presented in the left visual field (LVF) that is projected to the right hemisphere may be initially processed less efficiently (e.g., by serial orthographic analysis; Brand et al, 1983;Ellis et al, 1988;Eng & Hellige, 1984), and must be transferred to the left hemisphere via the corpus callosum, resulting in slower processing and/or some loss in fidelity. Consistent with this account, evidence that orthographic neighborhood (N) effects are larger and facilitatory in the LVF and weaker and inhibitory in the RVF (see Parker et al, 2021, for a review) may reflect stronger top-down activation from the word level within an interactive system for letter strings in the LVF. Words in the LVF would then suffer from slower and more error-prone bottom-up processing due to interhemispheric transfer.…”
Section: Visual Field Asymmetrymentioning
confidence: 89%
“…First, the experiments were conducted entirely online, limiting experimental control over participants' viewing conditions, hardware, operating system, or browser, which all can potentially affect timing performance. However, recent studies have demonstrated comparable performance in online and laboratory studies of lateralized word processing (Mills et al, 2022;Parker et al, 2021;Veldre et al, 2022) and masked priming (Angele et al, 2022), suggesting that online data collection is suitable for paradigms requiring precise timing.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%